Nature videos for PTSD: protocol for a mixed-methods feasibility study - Knaust, Thiemo; Felnhofer, Anna; Kothgassner, Oswald David; Reinke, Max; Browning, Matthew; Höllmer, Helge; Schulz, Holger (European journal of psychotraumatology, 2022)
Background: Given the prevalence of post-traumatic stress disorder (PTSD), particularly among military personnel, new treatment approaches are needed. One may be virtual relaxation interventions, especially 360-degree nature videos, since studies have demonstrated their relaxation effects for healthy participants. If these relaxation effects can be reproduced in patients with PTSD, they may offer a viable tool to reduce distress and hyperarousal. Objective: This research protocol describes a planned study that will examine the relaxation effects of 360-degree nature videos for patients with PTSD. It will also investigate whether these relaxation effects differ depending on the hardware immersion level (head-mounted display [HMD] vs. PC screen) in comparison to a control condition in which patients only listen to natural sounds and do not view a video. Finally, the effect of each intervention's dose duration (five vs. ten minutes) will be explored. Method: A counterbalanced, randomised, controlled, within-subject experiment will be conducted (sample size N = 36). Only soldiers aged 18 years or older with a primary diagnosis of PTSD will be included. Those with psychosis, substance dependence, a change in psychiatric medication within the last month, suicidal intent, and motion sickness will be excluded. All patients will experience the HMD, PC, and control conditions once for five or ten minutes. Self-reported relaxation measures will be collected before and after, and patients' skin conductance level, heart rate, and heart rate variability will be assessed during each condition. Semi-structured interviews will be conducted to examine the patients' experiences in detail. Conclusions: This feasibility study will provide initial evidence of whether viewing 360-degree nature videos via HMD or PC screen is relaxing for patients with PTSD and whether the effects are greater compared with the control condition. The study will also validate the dose duration and thereby informing a subsequent confirmatory interventional trial. Trial registration: DRKS00020277. This randomised controlled feasibility study will examine whether 360-degree nature videos are a suitable relaxation intervention for military personnel with post-traumatic stress disorder.